Propaganda and Transformation of Kejawen Society Beliefs: A Study in The Community of Sukowiyono Village: Propaganda dan Transformasi Kepercayaan Masyarakat Kejawen: Studi pada Masyarakat Desa Sukowiyono - Fauziah, Hanifah; Kalaloi, Abdul Fadli (Kanal: Jurnal Ilmu Komunikasi, 2024)
Abstract Propaganda is a communication used by an organized group to create active or passive participation in the actions of a mass audience. The author sees that propaganda occurs because of the existence of a government in an area. The government is the main reason for the transformation of values ​​in society. This happens because there is an activity carried out by the government to convey the government's own policies and objectives. The activities carried out can be in the form of propaganda. This research was conducted with the aim of describing the propaganda, in particular the techniques used as a means of transforming the Sukowiyono Village community. This research uses qualitative research methods using interview techniques as a way of collecting data. Interviews were conducted with religious figures and followers of Kejawen Islam in Sukowiyono Village. The research results show that the transformation of the Sukowiyono Village community gave rise to new Kejawen variations which were formed from the integration of new values ​​and Kejawen. Propaganda techniques are used to achieve goals effectively and efficiently. In the case of the transformation of the Sukowiyono Village community, several types of propaganda were carried out jointly and the media through da'wah was continuously used to disseminate information and government policies.